Échange généralisé : consistance et métamorphoses contemporaines d’un carrefour social (confins himalayens de Birmanie) - François Robinne (Moussons)
This reflection on the consistency of social crossroads takes as a case study a very specific social organization that is generalized exchange; the position defended here is that it serves as a “holding together” of the heterogenous landscape (Deleuze & Guattari 1980). In the first half of the twentieth century, the range of the Himalayan highlands bordering Burma/China/India gave rise to a series of monographic studies of the “tribes” and “groups”—the dominant terminology at the time—known as Chin, Naga, Kachin, etc. Their authors highlighted a recurring feature of a social organization based on asymmetrical exchange between “wife-givers” and “wife-takers” clans. From the second half of the twentieth century onwards, this vast corpus fueled a theoretical debate initiated by structural anthropology concerning the ‘categories indicative of matrimonial destiny’ around which “generalized exchange” is organised. The seminal works of Marcel Granet (1939), Claude Lévi-Strauss (1947) and Edmund Leach (1954), to name but a few, are considered in what follows in the light of the sudden disappearance—although the result of a long process—of the political systems provoked by the Burmese coup d’état of 1962. The aim of this article is to understand, on the basis of fieldworks carried out in the 2000s, the forms of neutralization, appropriation and other manipulations to which generalized exchange has been subjected since then. From a factual point of view, this is due to the emergence of political and religious centralisms with a hegemonic tendency; but also, from a methodological and conceptual point of view, to the trans-ethnic scope of generalized exchange and the choice of evaluating from this angle over the long term the consistency of a heterogeneous landscape.